2020
DOI: 10.1108/jhti-07-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tourist incivility, job stress and job satisfaction on tourist guides' vocational commitment

Abstract: PurposeThis empirical study explored how tourist incivility, job stress and job satisfaction affect tourist guides' vocational commitment.Design/methodology/approachData were collected via a questionnaire on a convenience sample of tourist guides during February–March 2018. A total of 172 valid questionnaires were collected, of which 100 were online and 72 face-to-face. The hypotheses were tested through multiple regression analyses.FindingsThe results show that job stress reduces both the affective and normat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 77 publications
0
24
0
1
Order By: Relevance
“…Furthermore, prior studies have revealed a clear relationship between organizational culture and JS (Mansoor and Tayib, 2010). Akgunduz and Eser (2020) confirmed that JS is positively correlated with AC; Ann et al (2014) found that JS exerted a negative effect on turnover intention. In other words, JS increases AC.…”
Section: Job Satisfaction and Affective Commitmentmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, prior studies have revealed a clear relationship between organizational culture and JS (Mansoor and Tayib, 2010). Akgunduz and Eser (2020) confirmed that JS is positively correlated with AC; Ann et al (2014) found that JS exerted a negative effect on turnover intention. In other words, JS increases AC.…”
Section: Job Satisfaction and Affective Commitmentmentioning
confidence: 77%
“…Furthermore, Al-Aameri (2000) investigated JS and AC among Saudi Arabian nurses and found a strong positive correlation between variables. Lastly, Akgunduz and Eser (2020) affirmed that JS is positively correlated to and Malek et al (2018) demonstrated that professional satisfaction is a predictor of AC. Accordingly, H3 is supported.…”
Section: Jhti 55mentioning
confidence: 85%
See 1 more Smart Citation
“…It also increases employees' revenge motivation and service sabotage (Cheng et al, 2020). Specifically, Akgunduz and Eser (2020) found that tourist incivility has a negative impact on normative commitment. It could be deduced that most of these studies were conducted in advanced societies with fewer studies in developing societies.…”
Section: Conceptual Modelmentioning
confidence: 96%
“…Tausing et al [25] add that workplace stress is a feature of the job style, such as the presence of a low level of decision making and a large number of demands. Akgunduz, Y. and Eser, S. [26] explained that job stress, which could be explained as a global and severe type of stress, affects employees' energy for performing their job and reduces their capacity. Wickramasinghe, V. [15] also suggests that employees who deal with complex work descriptions, role conflict, work uncertainty, and increased workplace stress could result in having less sustainable career satisfaction.…”
Section: Relationship Between Job Stress and Career Satisfactionmentioning
confidence: 99%